Magellan Spectroscopy of Active Galactic Nuclei in Low-mass Galaxies: Scaling Relations and a Triple-peaked Active Galactic Nucleus - Megan R. Sturm; Amy E. Reines; Jenny Greene; Sheyda Salehirad (The Astrophysical Journal)
In this work, we aim to further populate the low-mass regime of black hole (BH) scaling relations to better understand the formation and growth mechanisms of central supermassive BHs. We target six galaxies that have been previously identified as hosting active galactic nuclei (AGNs) based on optical spectroscopy from the Galaxy and Mass Assembly survey or the Sloan Digital Sky Survey with stellar masses reported to be M _⋆  < 5 × 10 ^9 M _⊙ . Using follow-up optical spectroscopy from the Magellan Echellette Spectrograph, we extract galaxy velocity dispersions ( σ _⋆ ) and estimate virial BH masses from broad H α emission. We find that the galaxies in our sample do not deviate significantly from either the M _BH − σ _* or M _BH − M _* scaling relations defined by higher-mass galaxies. Additionally, we identify one galaxy with triple-peaked [S II ], [N II ], H α , and H β emission lines. This spectral shape is not shared by [O III ] and, in fact, the [O III ] line appears to have distinct kinematics from the other emission lines. Incorporating the spatial distribution of the various emission lines, we find that the galaxy spectrum is consistent with a prominent central AGN driving an outflow, surrounded by an extended ring/disk of gas predominantly ionized by shocks and/or star formation. This work has implications for the demographics of BHs in low-mass galaxies and the role of AGN feedback.